Microwave-induced Synthesis of N-Substituted 1-Alkyl and 1-Aryl 3-Aminoisoquinolines - Méndez, Leticia Jesica (2017)
Background: Aminoisoquinolines are an important class of heterocyclic compounds. These compounds present a wide range of pharmacological properties including antimalaric, anticonvulsant and anti-inflammatory. Although several preparation routes may be found in the literature for the preparation of these compounds, many of these methods present difficulties, including laborious isolation methods, drastic conditions and extended reaction times. Methods: The synthesis of N-substituted 1-alkyl and 1-aryl- 3-aminoisoquinolines is developed through the reaction of 2-acylphenylacetonitriles with amines under microwave irradiation conditions. The reactions were performed in ethanol as a solvent without the use of catalyst. In parallel, these reactions were performed under identical conditions of temperature using P2O5/SiO2 as a catalyst in different amounts. Results: A series of N-substituted 1-alkyl and 1-aryl- 3-aminoisoquinolines were synthesized using microwave irradiation with as high selectivity, short reaction times and without the use of catalyst. The use of P2O5/SiO2 as catalyst under microwave irradiation conditions was not effective for these reactions. Conclusion: The results show an efficient method for the synthesis of N-substituted 1-alkyl and 1-aryl-3-aminoisoquinolines by the reaction of 2-acylphenylacetonitriles with amines using microwave irradiation. Some important advantages for this method include a strong decrease in reaction time, a good selectivity, and the absence of catalyst, with simplicity in operation and a benefit to the environment.